A Espacialização do programa de coleta seletiva de Ourinhos - Martelato, Bruno Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Law Nº12.305 of 2010, which establishing the National Policy of Waste Solids, propose regulatory instruments of management of solids waste with shared responsibility among the actors involved. Therefore, guidelines for a creation of actions focused in reduction and management of waste by the counties. Those guidelines must be descriptive by the Plan of Integrated Management of Waste Solids (PIMWS) of each county. The aim of this thesis is the analysis of the Selective Collection Program, as well as, the specialization of solids waste in the county of Ourinhos-SP. For the realization of this study were made different methodological procedures such as: bibliographic surveys, fieldwork for conducting interviews with the leaders Collectors of the Cooperative of Recyclable Materials Ourinhos (CCMR) - Recycle Ourinhos, the use of ArcGIS software 10:01It was necessary for the preparation of maps. One of the results was the extent of the selective collection program correspond to 100% of households in the urban area, we can see that each collection sector is an area of town and this area is not homogeneous

A Lei Nº12.305 de 2010, que institui a Política Nacional de Resíduos Sólidos, propõem instrumentos reguladores de manejo de resíduos sólidos com responsabilidade compartilhada entre os atores envolvidos, estabelecendo assim, diretrizes para a criação de ações voltadas para a redução e gestão dos resíduos por parte dos municípios. Essas diretrizes devem ser descritas através do Plano de Gerenciamento Integrado de Resíduos Sólidos (PGIRSO) de cada município. Esse trabalho tem como objetivo central a analise do Programa de Coleta Seletiva, bem como a espacialização dos resíduos sólidos no Município de Ourinhos-SP. Para a efetivação deste estudo foram efetuados diferentes procedimentos metodológicos, tais como: levantamentos bibliográficos, trabalho de campo para a realização de entrevistas junto as lideranças da Cooperativa de Catadores de Materiais Reciclável de Ourinhos (CCMR)- Recicla Ourinhos, a utilização do software ArcGis 10.01, foi necessária para a confecção dos mapas. Um dos resultados obtidos foi a abrangência do programa de coleta seletiva corresponder a 100% das residências do perímetro urbano, podemos observar que cada setor da coleta representa uma área da cidade e que essa área não é homogênea
Keywords: Coleta seletiva de lixo - Ourinhos (SP); Resíduos sólidos; Catadores de materiais recicláveis